Numerical optimization of self-compacting mortar mixture containing spent equilibrium catalyst from oil refinery - Nunes, Sandra (2017)
As the oil refining industries continue to grow, the production of waste catalysts generated in that process is expected to also increase. It would be of great value both economically and ecologically if these wastes could be reused as an addition in self-compacting concrete (SCC). This paper uses statistical factorial design approach, namely a central composite design, to conduct a proper experimental plan to design SCC mortar mixtures incorporating spent equilibrium catalyst (ECat), a waste generated by the oil refinery industry. The mathematical empirical models derived (which were also experimentally validated) revealed the influence of mixture design parameters, and their coupled effects, on the mortars' properties namely, deformability, viscosity, compressive strength, resistivity and ultrasonic pulse velocity. A numerical optimization technique was applied to the derived models to select the best mixture, which maximizes simultaneously durability and eco-efficiency and minimize cost, while maintaining self-compactability. The current study revealed that ECat can be successfully applied in SCC mortars, as a high volume cement replacement material (up to V-Ecat/Vp = 19.7%) due to its high pozzolanic activity. Nevertheless, for powder-type SCC5, cement/ECat blends must be combined with other finer additions to complete the powders distribution curve increasing the viscosity and stability of paste phase, in the fresh state.